La variació lingüística: el fet i la seva significació - Argenter, Joan A. (Caplletra. Revista Internacional de Filologia, 1998)
This study is a general presentation of the phenomenon of linguistic variation, from the point of view both of its empirical reality and of its semiotic, linguistic and socio-pragmatic analysis. We distinguish initially between the interest in research into the invariant form, which has characterized strict linguistics, and the orientation of sociolingüístics towards the study of variation; between theconcentration on the referential value of language as an arbitrary symbol and the concentration on the connotative value of languageas an index of social relations; between the limitation on the consideration of category alternation (allophony) and research intostructured variation (sociolingüístic variables); and between variation of a statistical character (such as the ones just mentioned) and variation based on discrete oppositions. The linguistic realities defined by the study of variation—styles, levels of language, naturalvarieties, registers—must be described not only in terms internal to the linguistic system but also in their relation to the social andsociocultural context; this terminological diversity reflects on occasions different linguistic modalities, and on others distinctmethodological approaches, among which we stress the importance of the ethnography.